Long-term legume green manure residue incorporation is more beneficial to improving bacterial richness, soil quality and rice yield than mowing under double-rice cropping system in Dongting Lake Plain, China - Nie, Jiangwen; Xie, Qingyun; Zhou, Yong; He, Feng; Yousaf, Muhammad; Zhu, Bo; Liu, Zhangyong (Frontiers in Plant Science, 2025)
IntroductionChinese milk vetch (vetch) is a promising winter cover crop that can reduce dependence on fertilizers and enhance crop productivity in southern China. However, its impact on soil microbial communities, soil quality, and rice yield, particularly when comparing the incorporation of green manure residue to mowing, remains insufficiently explored.MethodsTo address this gap, an 12-year field experiment was conducted in the Dongting Lake Plain, comparing three vetch management strategies under double-rice cropping system: winter fallow (CK), vetch rotation with residue incorporation (CMI), and vetch rotation with residue mowing (CMR). The soil quality index (SQI) was calculated based on abiotic [e.g., soil organic carbon (SOC), total nitrogen (TN), nitrate nitrogen (NO3–N)] and biotic [e.g., bacterial abundance, abundance-based coverage (ACE), Chao 1] factors. Results and discussionResults indicated that both the vetch management strategies significantly improved rice yield. Compared to CK, CMI and CMR enhanced early, late, and annual rice yields by 6.22%-10.77%, 7.50%-13.49%, and 7.03%-12.40%, respectively. Additionally, CMI improved soil redox potential, alkali-hydrolyzale nitrogen, ammonium nitrogen, and NO3–N, while CMR enhanced soil SOC, TN, NO3–N levels. Both CMI and CMR resulted in increases in the bacterial ACE index by 2.43%-2.53% and the Chao1 index by 0.92%-2.88% (P < 0.05). Furthermore, CMI reduced the Shannon index by 1.17% but increased the Simpson index by 19.35%, while CMR increased the Shannon index by 1.73% and elevated the Simpson index by 19.35% (P < 0.05). Principal component analysis indicated distinct bacterial community structures between CK and CMR. The dominant bacterial phyla included Proteobacteria, Chloroflexi, Nitrospirae, Acidobacteria, Bacteroidetes, and Actinobacteria. Notably, CMR exhibited lower relative abundances of Proteobacteria, Nitrospirae, and Acidobacteria compared to CMI. Compared to CK, CMI increased SQI by 6.92%, while CMR showed more modest improvements in soil quality. Moreover, a strong positive correlation between rice yield and SQI further confirmed the beneficial effect of vetch rotation on soil fertility. These findings underscore the potential of vetch rotation, particularly through vetch incorporation, to enhance soil quality and rice productivity, thereby offering valuable insights for sustainable agricultural practices.